The effect of timing of enteral nutrition support on feeding outcomes and dysphagia in patients with head and neck cancer undergoing radiotherapy or chemoradiotherapy: A systematic review. (August 2021) - Ye, Xiaodan; Chang, Yuan-Chin; Findlay, Merran; Brown, Teresa; Bauer, Judy
Summary: Background & aims: Patients with head and neck cancer (HNC) often require enteral nutrition (EN). This systematic review reports the effect of EN timing in patients with HNC undergoing curative-intent and definitive or adjuvant radiotherapy or chemoradiotherapy on tube feeding duration, tube-related complications and dysphagia. Methods: Randomised controlled trials (RCTs) published between January 2015–April 2020 were obtained from Medline, CINAHL and Embase. Study quality and certainty of evidence were assessed with Cochrane Risk-of-Bias and Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: Two RCTs (n = 265) in five manuscripts were included. The risk of bias was moderate in one RCT and low in the other RCT. Timing of EN (prophylactic vs. reactive) may have little or no effect on tube feeding duration or complications, however, the effect on dysphagia was uncertain. Certainty of evidence was low for short-term and moderate for long-term tube feeding duration, low for tube-related complications and very low for dysphagia. There was imprecision due to small sample sizes, heterogeneity in the definitions and protocols for prophylactic and reactive EN, variations in time points for outcome assessment and indirect dysphagia measures. Conclusion: Larger well-designed trials are warranted to increase certainty of evidence regarding EN timing in patients with HNC.